Novos táxons neotropicais de Desmiphorini (Coleoptera, Cerambycidae, Lamiinae) - Galileo,Maria Helena M. (2003)
New species described from Brazil: Curuapira tuberosa (Espírito Santo); Stereomerus maculatus (Bahia); Gyrpanetes oryba (Espírito Santo); Desmiphora (D.) santossilvai (Pará); Desmiphora (D.) uniformis (Bahia). Icublabia gen. nov., type-species, I. multispinosa sp. nov. from Ecuador (Napo) are described. Curuapira exotica Martins & Galileo, 1998, originally described from Venezuela, is recorded from Brazil (Amazonas, Rondônia and Mato Grosso).